The Factors of the Contraceptives Selection at the Sumbersari Public Health Center, Lumajang - Yulistiana Yulistiana; Ancah Caesarina Novi Marchianti; Candra Bumi (Alliance oh Health Activists (AloHA), 2020)
Side effects of the use of contraceptives have always been a problem complained by family planning acceptors. The side effects of family planning such as irregular menstruation, weight gain, nausea, dizziness, and vaginal discharge. This research was conducted in July-August 2019 to determine the factors causing the selection of contraceptives by family planning acceptors at the Sumbersari Public Health Center in Lumajang Regency. Researchers used a cross-sectional design. The sample were 98 family planning acceptors at the Sumbersari Public Health Center, Lumajang Regency, selected using cluster random sampling technique. Researchers used statistical regression tests to data analyze process. Statistical test results of factors that had a positive influence on the selection of contraceptive devices for family planning acceptors in the working area of Sumbersari Public Health Center were the number of children, knowledge of family planning, availability of tools, attitudes and husband's support; counseling performance in the majority of acceptors was good, and the majority of acceptors had a negative family planning history. Husband support and the number of children were the strong influence on the selection of contraception. Keywords: family planning; acceptor; contraceptive selection; factors